1986
DOI: 10.1093/ajcn/43.1.108
|View full text |Cite
|
Sign up to set email alerts
|

The effect of feeding route (IV or oral) on the protein metabolism of the neonate

Abstract: We have examined the effect of the route of feeding (intravenous versus enteral) on the protein metabolism of postsurgical human neonates. Twelve infants, birth weight 2.5 +/- 0.2 kg, gestational age 38 +/- 1 wk, were studied. The IV study was carried out 1-4 days after surgery at a postnatal age of 14 days and a weight of 2.6 +/- 0.2 kg. The repeat (oral) study was carried out 16 days later. Protein intakes were similar during both studies (2.7 g/kg/d). Energy intakes were within the requirement range for age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1987
1987
2004
2004

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…33 Their study compared the effect of feeding route (intravenous or enteral) on protein metabolism of the neonate and concluded that orally fed neonates utilise amino acids for synthesis more efficiently than total parenterally fed infants. 33 Early parenteral supply of amino acids is given to prevent protein loss but the present study clearly shows that enteral feeding is a far more efficient way of feeding preterm infants. Unfortunately, intestinal immaturity often impairs early full enteral feeding but our data suggest that maximal effort should be paid to initiate enteral feeding as soon as possible in preterm infants.…”
Section: Lysine Kinetics In Preterm Infantsmentioning
confidence: 99%
“…33 Their study compared the effect of feeding route (intravenous or enteral) on protein metabolism of the neonate and concluded that orally fed neonates utilise amino acids for synthesis more efficiently than total parenterally fed infants. 33 Early parenteral supply of amino acids is given to prevent protein loss but the present study clearly shows that enteral feeding is a far more efficient way of feeding preterm infants. Unfortunately, intestinal immaturity often impairs early full enteral feeding but our data suggest that maximal effort should be paid to initiate enteral feeding as soon as possible in preterm infants.…”
Section: Lysine Kinetics In Preterm Infantsmentioning
confidence: 99%
“…As a consequence, nutrient requirements for nitrogen and for amino acids, as well as for protein, are relatively high. Rates of body protein synthesis and nitrogen turnover are higher during enteral as compared to parenteral feeding, suggesting a more intensive synthesis and turnover of gastrointestinal (GI) proteins during enteral feeding ( Duffy & Pencharz 1986). Protein synthesis and turnover in new‐borns are reduced following food withdrawal and are enhanced by colostrum feeding, as shown in lambs ( Patureau‐Mirand et al .…”
Section: Introductionmentioning
confidence: 99%
“…Protein requirements suggested by various sources are given in Table 1. The effect of type of feeding route on protein metabolism in the neonate has been extensively reported elsewhere (Duffy & Pencharz, 1986;Pencharz et al 1989).…”
Section: Proteinmentioning
confidence: 99%